2013
DOI: 10.1103/physrevb.88.205406
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of state at Fermi level due to the formation of In-Sn heterodimers on Si(100)-2×1

Abstract: Structure and electronic properties of one-dimensional bimetallic In-Sn chains formed by codeposition on a Si(100)-2×1 surface are studied experimentally by means of scanning tunneling microscopy (STM) and scanning tunneling spectroscopy and theoretically using density-functional theory. The codeposition of In with a small amount of Sn allows separation of various In-Sn structures and their identification in empty-state STM images. A 16 × 2 supercell is employed to model an indium atomic chain in which one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In the analysis of single-atom alloys, palladium atoms isolated in a copper lattice were found to be almost electronically identical to their host atoms 113 . The study of In-Sn bimetallic chains on a single crystal silicon surface identified the preferential formation of In-Sn dimers stabilized by charge transfer to neighbouring In-In dimers, which induces the emergence of localized electronic states at, or slightly above, the Fermi level 114 .…”
Section: Electronic Structurementioning
confidence: 99%
“…In the analysis of single-atom alloys, palladium atoms isolated in a copper lattice were found to be almost electronically identical to their host atoms 113 . The study of In-Sn bimetallic chains on a single crystal silicon surface identified the preferential formation of In-Sn dimers stabilized by charge transfer to neighbouring In-In dimers, which induces the emergence of localized electronic states at, or slightly above, the Fermi level 114 .…”
Section: Electronic Structurementioning
confidence: 99%
“…As a representative example of the relevance of these methods toward understanding of pair-sites, isolated indium-tin and indium-indium dimers, as well as chains comprising these, were imaged by STM on atomically flat Si(001). 57 In this investigation, a combination of STS and the calculated local projected density of states was used to demonstrate that the local relative proximities of the dimeric species (and the associated charge transfer this facilitated) was determinative of whether the cluster could be characterized as metallic or semiconducting.…”
Section: Scanning Probe Techniquesmentioning
confidence: 99%
“…For instance, defined In−Sn heterodimers and In–In homodimers and chains of these on Si(001) have been investigated by STM. [ 262 ] More recently, partially dissociated water dimers on the O 2 evolution active hematite interface were confirmed through non‐contact atomic force microscopy (AFM), combined with other techniques. [ 263 ] CO adsorption on model single atom Ir adatoms on a Fe 3 O 4 (001) support was demonstrated by STM, non‐contact AFM and DFT ( Figure 20 a–c), [ 260 ] while in separate work Cu adatoms on the same support was proven by measuring the relative change in height of the Cu before and after CO adsorption via STM.…”
Section: Advanced Characterizationmentioning
confidence: 99%